Setting goals can help people with early stage dementia improve function. (20th June 2019) - Cook, Rob; Lamont, Tara; Martin, Rosie
The study: Clare L, Kudlicka A, Oyebode J R, et al. Goal-oriented cognitive rehabilitation for early-stage Alzheimer's and related dementias: the GREAT RCT. Health Technol Assess 2019;23:1-242. The trial was funded by the NIHR Health Technology Assessment Programme (project number11/15/04). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000767/goal-setting-in-early-stage-dementia-can-improve-function